(untitled) (translation. a transdisciplinary journal, 2022)
In line with the fact that multidiscipiinary studies as a whole have gained momentum these days, it seems that translation studies as a relatively young discipline has recently tried to embrace new findings from other disciplines to enrich and deepen itself. For instance, researchers in translation studies have successfully applied ideas from sociology, field theory (Bourdieu and Wacquant 1 992), actor-network theory (Latour 2005), applied mathematics, and game theory (von Neumann and Morgenstern 1 944; Myerson 1 997) to translation studies.